2012
DOI: 10.1177/0897190012442062
|View full text |Cite
|
Sign up to set email alerts
|

Triple Negative Breast Cancer: A Brief Review of its Characteristics and Treatment Options

Abstract: Triple negative breast cancer (TNBC), an aggressive variant of breast cancer, is characterized by lack of expression of the estrogen (ER) and progesterone receptors (PRs) and the human epidermal growth factor receptor (HER-2) that are commonly observed in other breast cancer subtypes. The TNBC subtype primarily occurs in younger women of African American or Hispanic descent and tumors tend to be high grade and initially responsive to chemotherapy. However, TNBC is characteristically aggressive with high recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 18 publications
0
91
0
2
Order By: Relevance
“…TNBC lacks an approved targeted therapy, and it is mainly treated with a combination of anthracyclines and taxanes (25). The high rate of relapse after treatment urges for the development of new targeted therapies for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…TNBC lacks an approved targeted therapy, and it is mainly treated with a combination of anthracyclines and taxanes (25). The high rate of relapse after treatment urges for the development of new targeted therapies for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options are very limited except with the traditional cytotoxic chemotherapy. 1 The systematic evaluation of different randomized clinical trials indicated that combining targeted agents with chemotherapy in triple negative breast cancer produced only modest gains in progression-free survival. 2 Therefore, a better understanding of the molecular basis of breast cancer progression and development of novel molecular targeted therapy is required for the better treatment of this breast cancer subtype.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, African American women have a higher incidence of triple-negative breast cancer than White Americans [7][8][9][10][11]. Triple-negative breast cancer is one of five subtypes of breast cancer which have been recognized to be luminal A (ER+ or PR+, HER2 -), luminal B (ER+ or PR+, HER2 +), HER2-overexpressing (ER-, PR-, HER-2+), basal-like (ER-, PR-, HER-2-, cytokeratin 5/6 + or epidermal growth factor receptor +), and unclassified or normal tumors [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that "basal-like" and "triple-negative" are not exactly synonymous (though they oftentimes overlap), as basal-like refers primarily to tumors defined by gene expression markers (including cytokeratins), whereas triple-negative is defined as having ER-, PR-, and HER2-status [7,9]. The triple-negative subtype is commonly referred to in the literature and will be the primary focus of this review.…”
Section: Introductionmentioning
confidence: 99%